Midterm Practice Solutions

Midterm Practice Solutions - PRACTICE PROBLEMS FOR MIDTERM:...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: PRACTICE PROBLEMS FOR MIDTERM: SOLUTIONS The test will be given on Monday, February 1 . It will be based on Homeworks 1-3 (Sections 1-5 and 7-8). In preparing for the test, you can practice solving the problems from the list below. In addition, take a look at the homework problems ( at least one problem on the midterm will come from the homework ), at the examples given in the textbook, and the the examples discussed in class. 1. Prove that, for any positive integer n , ∑ n k =1 k 2 k = ( n − 1)2 n +1 + 2. The proof proceeds by induction. The base of induction is easy to verify: plugging n = 1 into our identity, we see that 1 · 2 1 = 2 = (1 − 1)2 1+1 +2. To handle the step of induction, we need to show that, for m ∈ N , ∑ m k =1 k 2 k = ( m − 1)2 m +1 +2 implies ∑ m +1 k =1 k 2 k = m 2 m +2 +2. Note that ∑ m +1 k =1 k 2 k = ∑ m k =1 k 2 k +( m +1)2 m +1 . By the induction hypothesis, ∑ m k =1 k 2 k = ( m − 1)2 m +1 + 2, hence m +1 summationdisplay k =1 k 2 k = ( m − 1)2 m +1 + 2 + ( m + 1)2 m +1 = ( ( m − 1) + ( m + 1) ) 2 m +1 + 2 = 2 m · 2 m +1 + 2 = m 2 m +2 + 2 , which is what we need. 2. The sequence ( x n ) is defined by the following rule: x 1 = 3, and x n +1 = 2 x n − 1 for n ∈ N . Prove that, for any n ∈ N , x n = 2 n + 1. Let P n be the statement that x n = 2 n + 1. We use induction to show that P n is true for any n . The basis for induction consists of verifying that P 1 is true: x 1 = 3 = 2 1 + 1. To handle the induction step, we have to show that, for any m ∈ N , P m implies P m +1 (that is, P m +1 is true whenever P m is true). By our definition, x m +1 = 2 x m − 1. By the induction hypothesis, x m = 2 m + 1, hence x m +1 = 2 x m − 1 = 2(2 m + 1) − 1 = 2 · 2 m + 2 − 1 = 2 m +1 + 1 , which is precisely what we need. 3. Suppose x and y are positive elements of an ordered field, and x 2 = y 2 . Does it follow that x = y ?...
View Full Document

This note was uploaded on 05/08/2010 for the course MATH 140a taught by Professor Staff during the Winter '08 term at UC Irvine.

Page1 / 4

Midterm Practice Solutions - PRACTICE PROBLEMS FOR MIDTERM:...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online